Pengaruh Harga Jual Dan Biaya Distribusi terhadap Volume Penjualan Aspal Curah pada PT Sarana Aceh Utama di Lamreh Aceh Besar - Bukhari Usman; Darnelly Darnelly; Cut Delsie Hasrina; Nauval Julian Alfata (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study aims to determine the effect of selling prices and distribution costs on the volume of bulk asphalt sales at PT. Main Aceh Facilities in Lamreh Aceh Besar. Data collection techniques in this study were carried out by means of observation, interviews and documentation. The data analysis method used is multiple linear regression analysis. The research data processing was carried out using the SPSS for windows software model. The results showed that the selling price variable partially had a significant effect on the sales volume of bulk asphalt at PT. Sarana Aceh Utama, because the t-count value is greater than the t-table value or Ha is accepted, namely (17.876 > 1.672) and the significant level is below 0.05, i.e. (0.000 < 0.05) and the distribution cost variable partially has no significant effect on sales volume of bulk asphalt at PT. Sarana Aceh Utama, because the t-count value is smaller than the t-table value, namely (-3.661 <1.672) and the significant level is below 0.05, namely (0.001 <0.05) or Ha is rejected. The selling price and distribution cost variables simultaneously have a significant effect on the sales volume of bulk asphalt at PT. Sarana Aceh Utama, because the calculated F value is greater than the table F value, which is (1689.417 > 3.16) and the significant level is below 0.05, namely (0.000 < 0.05) or Ha is accepted.